Les enjeux d’une approche chronologique de la maison paysanne dans les Pays de la Loire - François Le Bœuf (In Situ)
This article is based on the observation of how masonry came to be used in the construction of peasant dwellings. This observation in the field raises the following questions. What was the ‘primitive’ nature of these constructions? What are the chronological indicators, different from one region to another, that permit precise dating for this appearance of masonry: archival sources, inscriptions, technical criteria, structural forms, nature of the masonry, stylistic considerations, surrounds of windows and doors, chimneys? This approach to the question can lead to a certain degree of precision in the dating of peasant dwellings, and implies a new appraisal of the ways this substitution took place. It is all the more interesting in so far as it raises interrogations about the uses of the peasant house, its architectural ‘brief’.